The Role of Organizational Culture in Teachers’ Professional Competence at Muhammadiyah Junior High Schools in Medan - Iman, Mujhirul; Wijaya, Candra; Halimah, Siti; Firmansyah, Firmansyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the synergistic relationship between school culture and the formation of teacher professionalism at Muhammadiyah Junior High School in Medan. This study is based on the assumption that the success of teacher competency development is not only determined by individual factors, but also by a positive work environment and visionary leadership. The research method used a quantitative approach with a correlational survey design. The research population included all 355 teachers at Muhammadiyah Junior High School in Medan City, with a sample of 217 respondents selected through simple random sampling. Data collection was conducted using a Likert scale questionnaire that had been tested for validity and reliability. Data analysis used path analysis to examine the direct and indirect contributions between variables. The results showed that school culture had a significant effect on teacher professionalism, while principal leadership reinforced this effect by creating a participatory and collaborative work climate. The combination of the two resulted in a higher increase in teacher professionalism compared to the effect of each variable separately. These findings emphasize the importance of building an adaptive school culture and transformative leadership as a strategy for improving the quality of education in private schools based on values.